Engineering ePTEN, an enhanced PTEN with increased tumor suppressor activities - Nguyen, Hoai-Nghia (National Academy of Sciences, 2014)
The signaling lipid phosphatidylinositol (3,4,5)-trisphosphate (PIP3) is a key regulator of cell proliferation, survival, and migration and the enzyme that dephosphorylates it, phosphatase and tensin homolog (PTEN), is an important tumor suppressor. As excess PIP3 signaling is a hallmark of many cancers, its suppression through activation of PTEN is a potential cancer intervention. Using a heterologous expression system in which human PTEN-GFP is expressed in Dictyostelium cells, we identified mutations in the membrane-binding regulatory interface that increase the recruitment of PTEN to the plasma membrane due to enhanced association with PI(4,5)P2. We engineered these into an enhanced PTEN (ePTEN) with approximately eightfold increased ability to suppress PIP3 signaling. Upon expression in human cells, ePTEN decreases PIP3 levels in the plasma membrane; phosphorylation of AKT, a major downstream event in PIP3 signaling; and cell proliferation and migration. Thus, the activation of PTEN can readjust PIP3 signaling and may serve as a feasible target for anticancer therapies.